1997
DOI: 10.1007/pl00006997
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines in Helianthus annuus L. during Germination under Salt Stress

Abstract: The level of the three main polyamines putrescine, spermidine, and spermine and the biosynthetic enzyme arginine decarboxylase (ADC) decreased in Helianthus annuus L. seedlings subjected to increasing (50, 100, and 150 mM) NaCl concentrations. The pattern of polyamines in control plants increased during the initial 72 h and then reached a plateau. The putrescine level showed an increase of 370% after 72 h of development. The lower salt treatment slightly diminished the overall polyamine content. The highest Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
3
18
0
2
Order By: Relevance
“…The present study provided strong evidence that SPM improved the growth of sweet sorghum under salinity. These findings were in agreement with a previous report which found that spermine was partially responsible for restoration of growth in seedlings treated with 150 mM NaCl, and was more effective than the putrescine (Benavides et al 1997).…”
supporting
confidence: 95%
“…The present study provided strong evidence that SPM improved the growth of sweet sorghum under salinity. These findings were in agreement with a previous report which found that spermine was partially responsible for restoration of growth in seedlings treated with 150 mM NaCl, and was more effective than the putrescine (Benavides et al 1997).…”
supporting
confidence: 95%
“…It has often been suggested that Put and derived PAs (Spd, Spm) may have distinct functions in response to stress. In several plant systems (Drolet et al 1986;Bar et al 1996;Benavides et al 1997) it has been shown that Spd and Spm act as anti-senescent compounds in response to stress, while Put produces either no effects or negative effects, such as depolarization of membranes, potassium leakage, tissue necrosis, and protein loss (Tiburcio et al 1990). So according to the present experiment, we can draw a conclusion that the decreasing of Spd and Spm, and the increasing of Put, deteriorated characters of Ni stress.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of Put in the intact plants and leaves in response to the osmotic or salt stresses has been reported by many authors [2,11,12]. However, others have reported either decrease or no changes at all in the Put level or in the level of all three major PAs in response to salt stress [13][14][15].…”
Section: Digital Signaturementioning
confidence: 81%